Application of The RFM Model and K-Means Clustering for Customer Segmentation in E-Wallet Top-Up Services - Sundari, Agus; Putra, Indra Syah; Sibuea, Nuraini (INFOMATEK, 2026)
The implementation of digital payment technology through e-wallet top-up services requires financial institutions to understand user characteristics and behavior comprehensively The objective of this study is to segment customers based on their e-wallet top-up behavior by analyzing 143,836 bill payment transaction records using the RFM (Recency, Frequency, Monetary) model combined with the K-Means clustering algorithm. The dataset contains more than one hundred thousand transaction entries, with RFM parameters representing the time since the last transaction, the frequency of top-ups, and the monetary value spent by users. The RFM scoring process is applied to quantify user activity levels before entering the clustering stage. The K-Means clustering model successfully grouped customers into three distinct segments. The first segment represents low-activity users, the second consists of moderately active customers with stable transaction behavior, while the third segment captures highly engaged users with the highest transaction frequency and value. Evaluation metrics, including a silhouette score of 0.64, a Calinski-Harabasz index of 21690.50, and a Davies-Bouldin score of 0.70, demonstrate strong clustering performance and reliable separation between groups. The findings provide valuable insights for designing service strategies, improving mobile banking system performance, and developing targeted marketing approaches tailored to each customer segment. This research highlights the potential of RFM based clustering as a decision-support tool for enhancing digital payment service optimization and customer engagement.